2021
DOI: 10.3389/fnins.2020.600423
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Thickness in Migraine: A Coordinate-Based Meta-Analysis

Abstract: Cortical thickness (CTh) via surface-based morphometry analysis is a popular method to characterize brain morphometry. Many studies have been performed to investigate CTh abnormalities in migraine. However, the results from these studies were not consistent and even conflicting. These divergent results hinder us to obtain a clear picture of brain morphometry regarding CTh alterations in migraine. Coordinate-based meta-analysis (CBMA) is a promising technique to quantitatively pool individual neuroimaging studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…A meta-analysis of GMV differences between CP-D and HCs was conducted with the seed-based d mapping (SDM) software package (version 5.15) in a standard process ( Radua et al, 2012 , 2014 ). The SDM approach used effect sizes to combine reported peak coordinates extracted from databases with statistical parametric maps, and it recreated original maps of the effect size of GMV difference between patients and HCs ( Chen et al, 2020 ; Sheng et al, 2020 , 2021 ). The SDM process was briefly described as follows: First, extracted peak coordinates and effect size (e.g., t -values and z -score) of differences in GMV between CP-D and HCs from each dataset and the z -score could be changed to t -values with the online tool on SDM website 1 ( Aoki and Inokuchi, 2016 ; Aoki et al, 2017 ); a standard MNI map of the GMV differences was then separately recreated for each dataset using an anisotropic Gaussian kernel.…”
Section: Methodsmentioning
confidence: 99%
“…A meta-analysis of GMV differences between CP-D and HCs was conducted with the seed-based d mapping (SDM) software package (version 5.15) in a standard process ( Radua et al, 2012 , 2014 ). The SDM approach used effect sizes to combine reported peak coordinates extracted from databases with statistical parametric maps, and it recreated original maps of the effect size of GMV difference between patients and HCs ( Chen et al, 2020 ; Sheng et al, 2020 , 2021 ). The SDM process was briefly described as follows: First, extracted peak coordinates and effect size (e.g., t -values and z -score) of differences in GMV between CP-D and HCs from each dataset and the z -score could be changed to t -values with the online tool on SDM website 1 ( Aoki and Inokuchi, 2016 ; Aoki et al, 2017 ); a standard MNI map of the GMV differences was then separately recreated for each dataset using an anisotropic Gaussian kernel.…”
Section: Methodsmentioning
confidence: 99%
“…Neuroimaging meta‐analysis method enables unbiased synthesis of results from numerous studies. Early neuroimaging meta‐analyses in migraine mostly summarized brain morphological alterations (Masson et al, 2021 ; Sheng et al, 2020 ; Wang, Wang, et al, 2020 ). To our knowledge, there has not yet been a quantitative meta‐analysis targeting the resting‐state local dysfunction of specialized brain regions in migraineurs.…”
Section: Introductionmentioning
confidence: 99%
“…Another study suggested other deep brain nuclei differences in the putamen and globus pallidus in migraine with aura ( Petrusic et al, 2019a ), with reduced volumes but larger brainstem volumes in migraine with aura compared to healthy controls ( Petrusic et al, 2019b ), suggesting that deep subcortical brain nuclei and brainstem structures may be altered in migraine with aura. The influence of disease activity, that is underlying headache frequency and disease duration, on structural imaging findings in migraine is unclear as various studies have reported conflicting findings ( Sheng et al, 2020 , 2021 ).…”
Section: Means Of Imaging Auramentioning
confidence: 99%